Analysis of Factors Affecting the Income of Culinary MSMEs in Medan Marelan District - Khairani Alawiyah Matondang; Bukit Buchori Siagian; Devi Cahya Putri (Universitas Negeri Semarang, 2026)
This study aims to analyze the influence of capital, labor, and technology on the income of culinary MSMEs in Medan Marelan District. The study involved 50 culinary MSME actors selected from a population of 857 businesses. The sample size was considered adequate for Partial Least Squares Structural Equation Modeling (PLS-SEM), as this method is suitable for exploratory studies with relatively small samples and complex relationships among variables. This research employed both primary and secondary data. Primary data were collected through questionnaires distributed to MSME actors, while secondary data were obtained from the Central Statistics Agency (BPS) and the Office of Cooperatives and MSMEs. Data analysis was conducted using SmartPLS 4 to examine the direct effects of capital, labor, and technology on MSME income. The findings reveal that all three variables have a positive and significant effect on income. Capital demonstrates the strongest contribution, indicating that business expansion and operational continuity among culinary MSMEs are highly dependent on financial capacity. Labor significantly supports productivity and service quality, while technology contributes to income improvement through operational efficiency and broader market reach. Simultaneously, the three variables significantly explain variations in MSME income. These findings highlight the importance of strengthening financial access, improving workforce quality, and encouraging technology adoption to support the sustainable development and competitiveness of culinary MSMEs.